1975
DOI: 10.1039/dc9755900063
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of surface active agents in a non-aqueous solvent

Abstract: Measurements have been made of the surface tension of solutions of sodium dodecyl sulphate, dodecyltrimethylammonium bromide, decanol, and of n-dodecyl and n-tetradecyl hexaoxyethylene monoethers in pure formamide and in salt solutions. Adsorbed films of the ionic surfactants exert low surface pressures (about 15 mN m-1 near the solubility limit) and exhibit no discontinuity characteristic of micellar aggregation. The monoethers exert surface pressures up to 25 mN m-I and show a critical micelle concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…It has, however, been observed with non-ionic surfactants in formamide by Couper et al [18]. Moreover, results for experiments in progress have shown that the parameters of hexagonal and lamellar phases in the CTAB/formamide system are lower than those for water, and are relatively small, given the chain length of CTAB.…”
Section: Micellization In the Binary Ctab/formamide Systemsmentioning
confidence: 86%
See 2 more Smart Citations
“…It has, however, been observed with non-ionic surfactants in formamide by Couper et al [18]. Moreover, results for experiments in progress have shown that the parameters of hexagonal and lamellar phases in the CTAB/formamide system are lower than those for water, and are relatively small, given the chain length of CTAB.…”
Section: Micellization In the Binary Ctab/formamide Systemsmentioning
confidence: 86%
“…mole -1 in water, and only-0.25 kJ. mole -1 in formamide [18]. Formamide thus behaves as a liquid that is highly structured round the hydrocarbon chains, and the low value of AH indicates that the exothermic chain interaction only just overcomes the endothermic destructuration of formamide.…”
Section: Micellization In the Binary Ctab/formamide Systemsmentioning
confidence: 94%
See 1 more Smart Citation
“…[f] From references [15,16], the data corresponding to the C 16 E 8 surfactant was obtained at 40 8C.…”
mentioning
confidence: 99%
“…[f] From (Couper et al, 1975;Jonstromer et al, 1990), the data corresponding to the C 16 E 8 surfactant was obtained at 40 °C.…”
Section: Surface Tension Measurementsmentioning
confidence: 99%